2020
DOI: 10.1111/asj.13372
|View full text |Cite
|
Sign up to set email alerts
|

Concentration patterns of antibacterial factors and immunoglobulin A antibody in foremilk fractions of healthy cows

Abstract: Antibacterial factors (AFs), such as antimicrobial peptides and proteins, belong to the innate immune system, which functions as soon as bacteria enter a living organism in a healthy condition. Innate immune reactions are much faster than those of the acquired immune system; a common immune system utilizing immunoglobulins (antibodies), which require a few days to respond after bacterial penetration. Antibodies react with bacteria in a specific manner, whereas AFs can attack a broad spectrum of bacteria and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The concentration of LAP in milk infected with S. aureus, Streptococcus bovis, Streptococcus dysgalactiae, and E. coli was found to be significantly higher than that in uninfected milk (Kawai et al 2013). Kitano et al (2020) states that the concentration patterns of LAP secreted in milk from the udders of healthy lactating cows follow the baseline data. These distinct concentration patterns might indicate various protective responses.…”
Section: Discussionmentioning
confidence: 70%
“…The concentration of LAP in milk infected with S. aureus, Streptococcus bovis, Streptococcus dysgalactiae, and E. coli was found to be significantly higher than that in uninfected milk (Kawai et al 2013). Kitano et al (2020) states that the concentration patterns of LAP secreted in milk from the udders of healthy lactating cows follow the baseline data. These distinct concentration patterns might indicate various protective responses.…”
Section: Discussionmentioning
confidence: 70%
“…It has been reported that inflammation-related factors, such as intramammary lipopolysaccharide administration [ 52 ] and intramammary infection of E. coli [ 41 ], increase the S100A7 concentration. It has also been pointed out that even in healthy milk, the S100A7 concentration is lowest in the first pre-squeezed milk, then it gradually increases [ 24 ], and it is also affected by the season [ 48 ]. From these studies, it was considered that the milk samples investigated in this study were not from mammary glands in an inflammatory state, and that known factors that influence the S100A7 concentration were sufficiently excluded.…”
Section: Discussionmentioning
confidence: 99%
“…S100A7, an AMP with a strong antimicrobial activity [ 16 , 17 ], which is first identified in the epithelial cells of human psoriasis skin [ 18 , 19 ], has been proved to play a critical role in IRR against the invasion and infection of pathogenic microorganisms. S100A7 can be detected in bovine milk [ 20 , 21 ] and serum [ 22 ]. In a bovine udder, the expression of S100A7 is common in teat skin and the streak canal [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…S100A7 can be detected in bovine milk [ 20 , 21 ] and serum [ 22 ]. In a bovine udder, the expression of S100A7 is common in teat skin and the streak canal [ 20 , 21 ]. But the expression of S100A7 was limited to bacteria-infected teat cisterns rather than the epithelial cells of the alveolus [ 17 , 23 ].…”
Section: Introductionmentioning
confidence: 99%